Determinants of BMT UGT Sidogiri Customer Loyalty: Does Cultural Factor Have an Essential Role? - Aris Yajid Bustomi; Mohammad Bintang Pamuncak; Diva Azka Karimah (AL-MUZARA'AH, 2026)
This study attempts to investigate the determinants of BMT UGT Sidogiri’s customer loyalty. As one of the biggest BMT in Indonesia, BMT UGT Sidogiri has played an essential role in developing its community’s economy through its business program. Factors such as brand image, profit-sharing, service quality, and cultural organization are employed in this study. This is because, BMT UGT Sidogiri is not only the largest BMT in Indonesia but also it initiated by Pesantren Sidogiri, one of the most respected pesantren in Indonesia which has unique cultural organization. This study finds that brand image has a negative-nonsignificant relationship with customer loyalty. Meanwhile, other variables such as service quality, profit-sharing, and culture have positive-significant relationship with customer loyalty that bridges by customer satisfaction. This study utilizes the partial least square-structural equation model (PLS-SEM) as a method. The result of the study is expected to contribute to the development of body of knowledge as well as practical implication of customer loyalty’s determinants, particularly on cultural factors which can benefits other microfinance institution based pesantren such as Sidogiri.